Local context-based English lessons: forging Northern Thai knowledge, fostering English vocabulary - Budsaba Kanoksilapatham, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Globalisation and regionalisation have culminated in the highlighted role of the English language for diverse realms of people across the world, including the ASEAN region and Thailand. To a number of scholars, the spread of English may result in negative consequences, possibly subjugating and menacing the national culture and identity of the English language learners. Thus, a burgeoning issue that emerges in the Thai context is how the students’ English language can be improved while maintaining their Thai identity. Given that young Thai learners tend to have relatively limited exposure to the national Thai identity due to their young age, this study focuses on a specific local identity – northern Thailand. This paper aims to demonstrate that a set of northern Thainess-based instructional innovations designed for Grade 4 students in the northern region of Thailand can boost not only northern Thainess knowledge but also English vocabulary knowledge related to northern Thailand. This set of the English lessons, as well as the corresponding northern Thainess and English vocabulary pretests and posttests, was constructed and implemented in four elementary schools in the northern part of Thailand. A comparison of the pretest and posttest scores on northern Thainess and vocabulary revealed that the students’ Thainess and vocabulary knowledge substantially increased, demonstrating the potential positive impacts of local Thainess-based instructional materials. The findings demonstrate a reverse perspective regarding the role of English in relation to Thai identity. Pedagogical implications regarding English material construction can be informed to ameliorate elementary English education in Thailand.